(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
Hypertext refers to the electronic links of texts. In the traditional texts, readers have to follow the linearity, and fixity of the book they are reading. Now computers give them a chance to escape this sort of restriction. Computer is a medium for the creation and the reading of texts. Hypertext or digital text, as we know, takes the form of a series of links. These links are adaptable, flexible, and interactive. They question the unity of the text, and the roles of both the reader and the author. Hence, hypertext requires redefining the concepts of author, reader, text, and structure–concepts of great importance to postmodernists. In addition, hypertext consists of fragments, pastiches, different styles and genres. It ignores boundaries, and addresses the mass. In brief, hypertext develops and brings to live many postmodern concepts such as decentering, intertextuality, writerly text and rejection of linearity and fixity of linear narrative. My paper is about hypertext in the light of postmodern theory.